2007
DOI: 10.1111/j.1399-3054.2007.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of temperature stress

Abstract: Plants possess inducible tolerance mechanisms that extend the temperature range for survival during acute temperature stress. The inducible mechanisms of cold acclimation and acquired thermotolerance involve highly complex processes. These include perception and signal transduction of non-optimal temperatures or their physical consequences on cellular components that program extensive modification of the transcriptome, proteome, metabolome and composition and physical structure of the cytoplasm, membranes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
314
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 455 publications
(352 citation statements)
references
References 78 publications
23
314
0
3
Order By: Relevance
“…Metabolite fingerprints to cold stress were obtained for Drosophila melanogaster individuals (Korn et al, 2010) and showed that the strategies to cold adaptation might be the same within all members of the kingdom. Janská et al (2011) confirmed all the significant metabolic variations, stirring in cold acclimatization, reenforcing the impression that the combination of cryoprotectant molecules is of great valve (Guy et al, 2008). Amongst these cryo-protectans, sugars, sugar alcohols and proline were exposed to be of higher significance.…”
Section: Metabolomics Profiling In Crop Plantssupporting
confidence: 49%
“…Metabolite fingerprints to cold stress were obtained for Drosophila melanogaster individuals (Korn et al, 2010) and showed that the strategies to cold adaptation might be the same within all members of the kingdom. Janská et al (2011) confirmed all the significant metabolic variations, stirring in cold acclimatization, reenforcing the impression that the combination of cryoprotectant molecules is of great valve (Guy et al, 2008). Amongst these cryo-protectans, sugars, sugar alcohols and proline were exposed to be of higher significance.…”
Section: Metabolomics Profiling In Crop Plantssupporting
confidence: 49%
“…Despite the suitability of this species for studying temperature stress (stress can be applied homogenously and rapidly to all cells, vegetative cells are undifferentiated, the genome is sequenced (82), gene families are smaller compared with higher plants), to our knowledge, there are no studies about cold stress in C. reinhardtii. Former studies in plant biology have described mechanisms implied in the cold response such as metabolomic changes (30,53,(83)(84)(85), integration of metabolomic and proteomic phenotypes (30), anatomical changes, sugar accumulation (15,26), late embryogenesis abundant (LEA), and heat shock (HSP) proteins mediating stabilization of membranes and proteins (65,86), and the activation of C-repeatbinding factor and dehydration responsive element-binding factor 1 (CBF/DREB) responsive pathways (2,9). Most of these studies have been focused on individual mechanisms with comparison of control versus stressed plants.…”
Section: Discussionmentioning
confidence: 99%
“…When winter rye is grown at warm temperature, plants are killed upon freezing at about −5°C, but upon exposure to low nonfreezing temperatures, they can survive freezing below −20°C. The molecular basis for this phenomenon, known as cold acclimation, is not completely understood, but includes changes in membrane cryobehavior, the production of cryoprotective proteins, and the biosynthesis of low molecular weight cryoprotectants such as sucrose, raffinose, and proline (2,3).…”
mentioning
confidence: 99%